2015
DOI: 10.1016/j.jcin.2015.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Left Atrial Appendage Closure With the Watchman Device

Abstract: LAA closure with the Watchman device is safe and feasible for stroke protection in patients with atrial fibrillation. Low ischemic events rates demonstrate its effectiveness during long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 18 publications
2
36
1
1
Order By: Relevance
“…The results of the PROTECT AF study showed that primary stroke risk reduction is comparable with percutaneous LAAC and anticoagulant treatment [8,9]. Currently, LAAC procedures are performed widely in clinical practice [6][7][8][9][10][11][12][13][14]. To date, the long-term efficacy of the LAAC procedure in patients with previous stroke has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the PROTECT AF study showed that primary stroke risk reduction is comparable with percutaneous LAAC and anticoagulant treatment [8,9]. Currently, LAAC procedures are performed widely in clinical practice [6][7][8][9][10][11][12][13][14]. To date, the long-term efficacy of the LAAC procedure in patients with previous stroke has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Thrombus formation on the device was detected in 2 of 41 patients who received dual antiplatelet therapy (DAPT) after their procedures. The authors concluded that LAA closure with WATCHMAN to be safe and conferred effective long-term cardioembolic protection in light of the low ischemic event-rates observed (9).…”
Section: Chamentioning
confidence: 98%
“…The study by Wiebe et al in 2015 in JACC Interventions is a timely study addressing these concerns (6). The authors reported results up to 5 years follow-up from a cohort of 96 patients who underwent percutaneous appendage closure using the Watchman device at a single center.…”
Section: Rocket-af Re-ly Aristotlementioning
confidence: 99%
“…Its efficacy for stroke prevention was tested in randomized clinical trials PROTECT AF and PREVAIL (3)(4)(5). In the December 2015 edition of JACC Interventions, Wiebe et al report long-term single center outcomes with the Watchman device (6). Before judging the efficacy of the Watchman device for stroke prevention, it is important to take a step back and understand the etiology of stroke in AF.…”
Section: Introductionmentioning
confidence: 99%